TRANSPORTASI DAN KETIMPANGAN WILAYAH DI PROVINSI JAWA TIMUR - Jose Rizal Joesoef; - Sulistiyanti; Andreas Prasetia (MediaTrend, 2016)
It is well understood that transportation improves the accessibility and transportation is needed in production and consumption activities. This study is aimed to describe the pattern of the movement of people and goods among districts/cities within the Province of East Java, to estimate the density of people and goods, and to measure the inequality of transport density. This study is also to test whether transport affects welfare. It is found that the Malang District and Surabaya City are the most destination of goods transport. Regression analysis shows that the density of transport only affects the welfare (as measured by the HDI) when together with other variables, namely poverty and GDP/capita. However, partial density of transport has no effect on the welfare.